Fascin in tooth germs: an immunohistochemical analysis. (2nd January 2018) - Alampally, Harishanker; Chandrashekar, Chethana; Rodrigues, Gabriel; Carnelio, Sunitha
Abstract: Development of a tooth is a complex process that involves three stages namely bud, cap and bell which results from the interaction of cells of oral mucosa and neural crest. During this process, oral and neural crest cells undergo various changes resulting in proliferation, apoptosis, morphological, and cyto-differentiation, which in turn would have changes in the cytoskeletal framework of the cell that includes actin and tubulin. Fascin is an actin-bundling protein that cross-links individual actin filaments into straight, compact, stiff bundles, which are crucial for the formation of finger-like membrane protrusions and aids in cell migration but is less explored in tooth germs. The aim of this study was analyze the expression and distribution of fascin in various stages of human tooth germs. Twenty human tooth germs were stained with hematoxylin and eosin and with immunohistochemical staining for fascin. Strong membranous expression for fascin was observed in various stages with decreased expression in stellate reticulum from cap stage to bell stage. Also, outer enamel epithelial cells had a weak fascin expression. Although cells of dental papilla did not express fascin in early cap stage of tooth development, strong expression of fascin was observed in later bell stages. It was also observed the inner enamel epithelium close to areas of calcification showed a decreased expression. Thus, the expression of fascin in various stages of tooth development being site and time specific may play an important role in cell remodulation.